1996
DOI: 10.1073/pnas.93.16.8253
|View full text |Cite
|
Sign up to set email alerts
|

A hyperphosphorylated form of the large subunit of RNA polymerase II is associated with splicing complexes and the nuclear matrix.

Abstract: A hyperphosphorylated form of the largest subunit of RNA polymerase II (pol IIo) is associated with the pre-mRNA splicing process. Pol IIo was detected in association with a subset of small nuclear ribonucleoprotein particle and Ser-Arg protein splicing factors and also with pre-mRNA splicing complexes assembled in vitro. A subpopulation of pol hIo was localized to nuclear "speckle" domains enriched in splicing factors, indicating that it may also be associated with RNA processing in vivo. Moreover, pol IIo wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
223
2
5

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(249 citation statements)
references
References 35 publications
18
223
2
5
Order By: Relevance
“…Additionally, there is a need for new assays to probe the connections between promoter regulation and premRNA processing decisions. As RNA Pol II-RNA binding protein complexes may be reorganizing during mRNA synthesis, these data are consistent with models in which cotranscriptional assembly of RNPs is a dynamic process (Mortillaro et al 1996;Wetterberg et al 2001;Custodio et al 2004;Ujvari and Luse 2004;Yu et al 2004). …”
Section: Significance Of Genomic Localization Of Rna Binding Proteinssupporting
confidence: 73%
See 2 more Smart Citations
“…Additionally, there is a need for new assays to probe the connections between promoter regulation and premRNA processing decisions. As RNA Pol II-RNA binding protein complexes may be reorganizing during mRNA synthesis, these data are consistent with models in which cotranscriptional assembly of RNPs is a dynamic process (Mortillaro et al 1996;Wetterberg et al 2001;Custodio et al 2004;Ujvari and Luse 2004;Yu et al 2004). …”
Section: Significance Of Genomic Localization Of Rna Binding Proteinssupporting
confidence: 73%
“…These early genomic efforts suggested that, similar to DNA binding proteins, functional groupings of genes are being bound by RNA binding proteins perhaps as post-transcriptional operons (Keene and Tenenbaum 2002). However, it is not known at which stage of RNA processing these operons are established.Much of pre-mRNA processing is coupled to transcription both physically and functionally, potentially through interactions with the C-terminal domain (CTD) of RNA polymerase II (RNA Pol II) (Mortillaro et al 1996;Yuryev et al 1996;Kim et al 1997). The CTD is phosphorylated as transcription begins.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the phospho-Ser2 CTD has been shown to interact with the Ser/Arg-rich (SR) proteins (e.g. SF2/ASF and SC35), Spt6, and snRNP particles (153)(154)(155)(156)(157). Providing visual support for this recruitment model, Pol II with the complete, but not a truncated CTD, was found to recruit splicing factors to sites of active transcription in living cells (158).…”
Section: Splicingmentioning
confidence: 93%
“…However, CTD might also play a role by providing a platform for the splicing machinery and even regulate the choice of alternative exons by increasing the local concentration of proteins (de la Mata and Kornblihtt, 2006). Splicing factors including small nuclear ribonucleoprotein particles (snRNPs) and non-snRNP proteins such as the serine/argininerich (SR) protein family are associated with pol IIo but not with pol IIa (Mortillaro et al, 1996;Kim et al, 1997). The arginine-serine rich (RS) domain of the SR family protein is essential for recruitment to the phosphorylated CTD (Misteli and Spector, 1999).…”
Section: Deciphering the Ctd Codementioning
confidence: 99%